G10 Colonic volume changes in paediatric constipation compared to normal values. (12th September 2022) - Sharif, Hayfa; Hoad, Caroline L; Abrehart, Nichola; Gowland, Penny A; Spiller, Robin C; Kirkham, Sian; Loganathan, Sabarinathan; Papadopoulos, Michalis; Benninga, Marc A; Devadason, David; Marciani, Luca
Abstract : Introduction/Background: Functional constipation (FC) in childhood is common, with a prevalence estimated around 10%. To date, relatively little is known about colonic volume in children with FC. Aim: The primary aim of this study was to measure colonic volume in children of different ages with FC and also provide initial normal range values for healthy controls using MRI. 1 Subjects and Methods: Nineteen healthy volunteers (age 16±2 y) and 16 patients with FC (age 11±3 y) participated in a recent MRI study investigating whole gut transit time (WGTT) under Ethics approval 17/WM/0049. 2 The image data was analysed here for colon volumes as follows. Individual regional colon volumes were manually segmented on each slice using Medical Image Processing, Analysis and Visualisation software (MIPAV, NIH, Bethesda). The colon was divided into 4 regions: ascending colon (AC), transverse colon (TC), descending colon (DC) and sigmoid colon and rectum region (SC-R) and colon volume data were corrected for body surface area (BSA) using the Mosteller formula. Linear regression was used to assess the strength of the relationship between colon volume and WGTT. Results: The total colonic volume corrected for BSA ( figure 1, right panel) was 309mL (243–384mL) median (IQR) for the young patients with constipation, significantly larger than that for the healthy controls 227mL (180–263mL) (p=0.0081). Regional colon volumes showed that the larger increase was between controls and patients was in the SC-R region (p=0.0410 Mann-Whitney one-tailed test) with 9 constipated patients having SC-R volume above the 95% CI of the control values. There was a positive correlation between the total colonic volume and WGTT, coefficient of correlation R=0.56, p=0.0005. Summary: In our study the total colon volume was found to be larger in the paediatric patients with FC than in healthy controls, where 63% of patients with FC had a colonic volume above the 75% centile of normal control values and 25% of patients had the colon volume above the 95th centile (upper limit of normal) of the healthy control values. There are no similar studies to compare our data against. We also found a moderate but significant correlation of transit with colonic volume. Conclusion: This study provides novel data on colonic volume in paediatric functional constipation patients and initial normal range values. MRI allowed us to study the undisturbed, un-prepared colon in its physiological state. Further work is needed to increase the number of participants studied and continue to investigate the relationship between colonic volume and WGTT. References: Sharif H, et al. Diagnostics 2021;11 :974. Sharif H, et al. JPGN 2020;71 :604–611.